Tunable multi-wavelength generation using InGaAsP/InP microring resonator with detectable resonance wavelength shift due to a sensing cladding section - Amiri, I.S.; Ariannejad, M.M.; Ahmad, Harith (Elsevier, 2016)
In this research, we use the time-domain travelling wave (TDTW) method to model and simulate a microring resonator (InGaAsP/InP) waveguide based on resonance wavelength shifts. A change of the refractive index of the cladding results in a change of the effective index of the mode propagating within the microring resonator, where it can be observed by a shift of the resonance wavelength, thus providing a tuning mechanism. The total length of the microring resonator is 100μm, with a varying refractive index along 40μm of the cladding section. The Q-factor of the microring resonator is 4.5 × 105, showing high performance of the system. The largest resonance wavelength shift is 3.7nm and is obtained when the medium of the cladding is air.